Significance of monitoring plasma concentration of voriconazole in a patient with liver failure: A case report. Issue 42 (October 2017) - Liu, Xiaoyan; Su, Haibin; Tong, Jingjing; Chen, Jing; Yang, Haozhen; Xiao, Long; Hu, Jinhua; zhang, Lina
Abstract: Rationale: Invasive pulmonary aspergillosis is associated with significant morbidity and mortality in patients with liver failure. Voriconazole (VRCZ) is recommended as a primary therapeutic agent for the treatment of invasive aspergillosis and metabolized in the liver. Now, data are still lacking on the safety and appropriate dosage of VRCZ in patients with liver failure. Here, we report a representative case of invasive pulmonary fungal infection in a patient with liver failure who was treated with low-dose VRCZ. Patient concerns: A 21-year-old man, presented with subacute liver failure caused suspected by viral infection, was admitted on June 22, 2014. Liver function was not improved by the treatment of gancicolovir and methylprednisolone. The patient presented with fever, cough, and hyperpyrexia on July 14. Laboratory tests revealed raised neutrophil percentage (82.1%, normal range [NR] 50–70), international normalized ratio (INR) (2.32, NR 0.8–1.2) and levels of serum lactic acid (4.308 mmol/L, NR 0.6–2.2), alanine transaminase (165 U/L, NR 0–40), aspartate transaminase (99 U/L, NR 8–40), and total bilirubin (654 mmol/L, NR 3.4–20.5). Furthermore, CD4+ T cell, CD8+T cell, and B cell count were low (169, 221, and l8/mL, respectively). Sputum smear microscopy for bacteria was negative, but the direct observation for fungal elements was positive. Thoracic CT scan revealed bilateral pulmonary high-density shadow. Sputum cultures were positive 2 days later with the presence of Aspergillus fumigatus. Diagnoses: Therefore, this patient diagnosed with suspected pulmonary a spergillosis. Interventions: VRCZ was used on July 15th and its dosage was 400 mg twice on day 1 followed by a maintenance dose of 100 mg twice daily according to drug usage instruction. However, some side effects, such as tremors, lips twitching, and hair loss, occurred. Plasma VRCZ trough concentration was 8.1 mg/mL which was much higher than the recommend level. Therefore, VRCZ dosage was adjusted according to its plasma concentration. VRCZ plasma concentration fluctuated between 2.5 to 4.7 mg/mL when its dosage was 100 mg once daily and side effects disappeared. Outcomes: VRCZ was administered for 2 months. This patient's symptoms and liver function were improved. A follow-up CT scan performed at the end of VRCZ therapy indicated that the high-density shadow had diminished. Lessons: This case demonstrated that low-dose VRCZ (maintenance dose, 100 mg/day) can achieve effective plasma concentration and reduce side effects without liver damage. We believe that VRCZ is safe to be administered in patients with liver failure, but its plasma concentration should be carefully monitored.